Automatic Intruder Combat System: A way to Smart Border Surveillance - Singh, Dushyant Kumar; Kushwaha, Dharmender Singh (Defence Science Journal, 2016)
Security and safeguard of international borders have always been a dominant issue for every nation. A large part of a nation’s budget is provided to its defense system. Besides wars, illegal intrusion in terms of terrorism is a critical matter that causes severe harm to nation’s property. In India’s perspective, border patrolling by Border Security Forces (BSF) has already been practiced from a long time for surveillance. The patrolling parties are equipped with high-end surveillance equipments but yet an alternative to the ply of huge manpower and that too in harsh environmental conditions hasn’t been in existence. An automatic mechanism for smart surveillance and combat is proposed in this paper as a solution to the above-discussed problems. Smart surveillance requires automatic intrusion detection in the surveillance video, which is achieved by using optical flow information as motion features for intruder/human in the scene. The use of optical flow in the proposed smart surveillance makes it robust and more accurate. Use of a simple horizontal feature for fence detection makes system simple and faster to work in real-time. System is also designed to respond against the activities of intruders, of which auto combat is one kind of response.